2022
DOI: 10.3390/diagnostics12020555
|View full text |Cite
|
Sign up to set email alerts
|

Improving Visual-Patient-Avatar Design Prior to Its Clinical Release: A Mixed Qualitative and Quantitative Study

Abstract: Visual-Patient-avatar, an avatar-based visualisation of patient monitoring, is a newly developed technology aiming to promote situation awareness through user-centred design. Before the technology’s introduction into clinical practice, the initial design used to validate the concept had to undergo thorough examination and adjustments where necessary. This mixed qualitative and quantitative study, consisting of three different study parts, aimed to create a design with high user acceptance regarding perceived p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…After a 6-min educational video (Additional File 1 ), all visualizations eventually reached an inter-rater reliability of > 94%. In a study performed with 30 participants, > 70% of the visualizations of the revised design used in the product were intuitively recognizable without any training [ 50 ].…”
Section: User-centered Technologies For Patient Monitoringmentioning
confidence: 99%
“…After a 6-min educational video (Additional File 1 ), all visualizations eventually reached an inter-rater reliability of > 94%. In a study performed with 30 participants, > 70% of the visualizations of the revised design used in the product were intuitively recognizable without any training [ 50 ].…”
Section: User-centered Technologies For Patient Monitoringmentioning
confidence: 99%
“…In a previous effort to refine the design of the Visual Patient Avatar prior to its introduction into the clinical setting, users were asked to provide feedback on their perceptions of an earlier version of the technology [34]. Compared to the user perceptions of the Visual Patient Avatar prior to its redesign, this study revealed that the updated version of the technology evoked positive feedback from numerous participants concerning the presentation of specific parameters.…”
Section: Discussionmentioning
confidence: 94%
“…In two visualisation technologies we previously developed, Visual Patient for patient monitoring and Visual Clot for rotational thromboelastometry, we found the positive effects observed in computer-based simulation studies [ 17 , 20 , 21 , 22 , 23 , 24 , 25 , 30 ] to persist in high-fidelity simulation studies [ 18 , 31 , 32 , 33 ]. The substantial effect sizes observed to date with these technologies demonstrates their significant potential to improve decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that visualisations that have a logical relation to reality can be recognised even without an instructional video [ 31 ]. This quality is desirable because there is often little time to obtain explanations in real life.…”
Section: Discussionmentioning
confidence: 99%